2014
DOI: 10.2196/jmir.3397
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Internet Forums to Evaluate Reactions to the Introduction of Reformulated OxyContin to Deter Abuse

Abstract: BackgroundReformulating opioid analgesics to deter abuse is one approach toward improving their benefit-risk balance. To assess sentiment and attempts to defeat these products among difficult-to-reach populations of prescription drug abusers, evaluation of posts on Internet forums regarding reformulated products may be useful. A reformulated version of OxyContin (extended-release oxycodone) with physicochemical properties to deter abuse presented an opportunity to evaluate posts about the reformulation in onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…[124] Despite discussion of recipes (32 of which were deemed feasible, i.e., able to abuse), the frequency of posts reporting abuse via these recipes was low and decreased over time. Of the 5677 posts mentioning the abuse-deterrent reformulation, 498 reported abuse (41 reported injecting and 128 reported snorting).…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
“…[124] Despite discussion of recipes (32 of which were deemed feasible, i.e., able to abuse), the frequency of posts reporting abuse via these recipes was low and decreased over time. Of the 5677 posts mentioning the abuse-deterrent reformulation, 498 reported abuse (41 reported injecting and 128 reported snorting).…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
“…In a survey of oral abusers, 42% reported manipulation (e.g., chewing, dissolving in mouth) of crush-resistant tablet formulations prior to oral administration [3]. Further, a review of Internet forums found 32 potentially feasible recipes to overcome the crush-resistant properties of OxyContin [17]. Tampering methods to compromise the OxyContin formulation are not always sophisticated, and often chewing tablets before oral administration is used to attempt to elicit rapid onset of euphoria sought by drug abusers [17].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a review of Internet forums found 32 potentially feasible recipes to overcome the crush-resistant properties of OxyContin [17]. Tampering methods to compromise the OxyContin formulation are not always sophisticated, and often chewing tablets before oral administration is used to attempt to elicit rapid onset of euphoria sought by drug abusers [17]. It is thought that novice drug abusers often begin with oral administration and evolve their drug use habits to chewing, snorting and eventually injection, a progression that is associated with more dire outcomes [18].…”
Section: Discussionmentioning
confidence: 99%
“…(Boyce & Hoag, 2014), fewer than one-fifth (15%) of the reported methods in the present study were based on internet sources. This in itself may reduce the potential for harm to the consumer: McNaughton et al (2014) reported only a small number of posts identifying preparation methods for tampering post-introduction; only 9% of posts related to potentially feasible manipulation techniques. There were few distinguishing characteristics of those who tampered with the reformulated oxycodone compared with those who tampered only with the original oxycodone formulation, with similar socio-demographic profiles, mental and physical health, and, most importantly, levels of pharmaceutical opioid dependence.…”
Section: Discussionmentioning
confidence: 99%
“…US studies have examined levels of tampering (Butler et al, 2013) and perceived attractiveness . Whilst there has been analysis of internet posts regarding methods for tampering (McNaughton et al, 2014, this study represents, to the author's knowledge, the first in-depth systematic investigation of self-reported methods of tampering and their perceived success. The high retention rate for Wave 2 interviews, comprehensive assessment of pharmaceutical opioid tablet forms and sizes, and emphasis on confidentiality and anonymity are strengths of this study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%